2021
DOI: 10.1177/08959048211019975
|View full text |Cite
|
Sign up to set email alerts
|

YPAR Dreams Deferred? Examining Power Bases for YPAR to Impact Policy and Practice

Abstract: Practitioners and scholars have argued that youth participatory action research (YPAR) challenges systemic injustice in education, as youth and adults research mechanisms of oppression and propose recommendations. However, oftentimes YPAR does not lead to new policies, as institutional decision-makers ignore youth’s moral pleas and empirical evidence. In this conceptual article, we propose a consideration of the ways in which YPAR can mobilize power bases using youth organizing and institutionally sanctioned d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…Arnulfo's principal heard his poem and decided to immediately change the policies of flags at school, explicitly including the Mexican flag as an acceptable symbol of pride and culture. Researchers have also suggested that intergenerational CPAR coupled with organizing strategies or placing youth in positions with institutional power might be a viable way to mitigate the politics in these contexts-at times, this requires the social and political capital of adults (Bertrand & Lozenski, 2021). Building on the concerns raised in the extant literature, we aim to highlight the messy entanglements of politics when CPAR strives to inform policies and practices in schools and society.…”
Section: Cpar: Informing Policies While Negotiating the Politicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arnulfo's principal heard his poem and decided to immediately change the policies of flags at school, explicitly including the Mexican flag as an acceptable symbol of pride and culture. Researchers have also suggested that intergenerational CPAR coupled with organizing strategies or placing youth in positions with institutional power might be a viable way to mitigate the politics in these contexts-at times, this requires the social and political capital of adults (Bertrand & Lozenski, 2021). Building on the concerns raised in the extant literature, we aim to highlight the messy entanglements of politics when CPAR strives to inform policies and practices in schools and society.…”
Section: Cpar: Informing Policies While Negotiating the Politicsmentioning
confidence: 99%
“…The various contexts we have described in these counterstories, for example, schools, districts, universities, and non-profit organizations, are steeped in systems and organizational structures that reinforce white supremacist and settler-colonial ideologies (Teixeira et al, 2021). Therefore, the very nature of pushing forward policy changes that disrupt the status quo will engender youth researchers wading through the politics of it all (Bertrand & Lozenski, 2021). Consequently, it is imperative that adult facilitators prioritize the humanity of our young people and recognize that justice-work for policy change necessitates employing an affective labor in how we support and care for our youth researchers.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…At the opposite end of our proposed continuum of harms is the transactional operationalization of youth-adult partnerships as simply a way to satisfy inclusion or diversity requirements (Hipolito-Delgado, 2023;Lac et al, 2019), resulting in the tokenization of current and former foster youth where benefits to the system are prioritized over youth needs and priorities. Moreover, when benefits to the system are identified, they often extend only to YA storytelling for child welfare workers' morale boosts or as examples of what effective casework might lead to (Bertrand & Lozenski, 2023). These realities similarly lead to the exclusion of the myriad of other things YA can offer, such as firsthand knowledge of problems, increased agency capacity, peer mentorship, training, and more (Augsberger et al, 2019;Lac, 2019;Ozer et al, 2020).…”
Section: Ya As "Storytellers" Only -Listening To Stories Without Hear...mentioning
confidence: 99%
“…The paucity of student voice in U.S. schools might be surprising, since it has the potential for such strong outcomes for young people; yet the lack of empowerment of teachers or students in most U.S. educational spaces points to the ways in which school systems implicitly and explicitly impede opportunities for social justice. Research increasingly addresses concerns about “adultism” as a form of oppression (Bertrand & Lozenski, 2023; Mitra, 2006; Mitra, 2018; Rodela & Bertrand, 2022; Salisbury et al, 2020). Indeed, positioning students as change agents requires pushing against the expected power dynamics to create “radical collegiality” (Fielding, 2011)—creating counter-normative ways of acting between young people and adults.…”
Section: Student Voice As Critical Distributed Leadershipmentioning
confidence: 99%